Disparities in the Use and Quality of Alcohol Treatment Services and Some Proposed Solutions - Mulia, Nina (2014)
OBJECTIVE: To assess racial/ethnic disparities in access to quality alcohol treatment services for risky drinking and alcohol problems in the United States, and to simulate strategies to narrow the gap. METHODS: Three-year longitudinal data from the National Epidemiologic Survey on Alcohol and Related Conditions (NESARC) were analyzed to examine the receipt of alcohol interventions in primary care and specialty treatment settings, consistent with published clinical guidelines. We compared US racial/ethnic minority and non-minority adults who were at-risk drinkers or had alcohol problems at baseline (N=9116). Simulation analyses projected how disparities in treatment services utilization might change if guidelines promoted care in more varied health and human service settings. RESULTS: Compared to whites, racial/ethnic minorities had two-thirds the odds of receiving an alcohol intervention over the three-year period (OR=0.62, 95%CI: 0.39–0.98). This disparity increased after adjusting for socioeconomic and clinical confounders (AOR=0.47, 95%CI: 0.28–0.80). The most pronounced disparities were observed among U.S.-born and foreign-born Hispanics (vs. whites). Simulation analyses suggested that these disparities could be partially mitigated by extending care to non-medical service venues. CONCLUSIONS: Given limited capacity and barriers to using specialized addiction programs, current efforts to extend evidence-based alcohol interventions into medical settings address an important need. In doing so, however, racial/ethnic disparities in access to high-quality treatment are likely to increase. Partial solutions may be found in expanding the range and quality of alcohol-related services provided in alternative delivery sites, including faith-based and social service institutions.